Urban participatory planning approaches in capital cities: The Lisbon case - Medeiros, E. (European Planning Studies, 2022)
This paper assesses participatory urban planning in Lisbon, based on the ongoing urban development plan. The results of the qualitative analysis on the urban governance and participatory process covering a two-year period (2010–2012), in which the urban development plan was discussed, suggest a highly participatory urban planning process, involving not only individual citizens but also schools, NGOs, business, academia, surrounding municipalities and several other types of stakeholders. How far the common citizen influenced the development of the final version of the urban plan is, however, open for debate. On a positive note, there is clear evidence of institutional learning and democratic openness from the presented case, which can serve as a good example for other capital cities on how to organize urban planning participatory processes.